Redox-responsive hyperbranched poly(amido amine) and polymer dots as a vaccine delivery system for cancer immunotherapy. Issue 48 (28th November 2017) - Lv, Meng; Li, Sha; Zhao, Haijie; Wang, Kewei; Chen, Qianqian; Guo, Zhong; Liu, Zonghua; Xue, Wei
Abstract : PAA-PEI600 and partially carbonized PAA-PEI600 -derived polymer dots were designed as vaccine carriers to deliver the model antigen protein ovalbumin (OVA). Abstract : In order to enhance the cellular immune response of vaccines, numerous vaccine delivery systems have been developed, especially cationic nanoparticle carriers. Cationic polymer dots (PDs) have been widely used for biomedical imaging and drug delivery due to their excellent photoluminescence, small size and abundant positive charge. In this study, polyethyleneimine (600 Da) (PEI600 )-modified redox-responsive hyperbranched poly(amido amine) (PAA-PEI600 ) and partially carbonized PAA-PEI600 PDs were designed and prepared as vaccine carriers to deliver the model antigen protein ovalbumin (OVA). Then, OVA-specific immune responses induced by PAA-PEI600 /OVA and PDs/OVA nanoparticles were evaluated in vivo . The results suggest that the PAA-PEI600 /OVA and PDs/OVA nanoparticles enhanced OVA-specific immune responses when compared to OVA alone. Further, PDs/OVA nanoparticles induced more potent OVA-specific cellular immune responses, including higher levels of the OVA-specific IgG2a/IgG1 antibody ratio, splenocyte proliferation, IL-12 and IFN-γ cytokines, maturation of dendritic cells, effector memory CD4 + T cells and CD8 + T cells as well as cytotoxic T lymphocytes (CTLs) than PAA-PEI600 /OVA nanoparticles did. Moreover, subcutaneously injected PDs/OVA nanoparticles significantly inhibited tumor growth of the mice bearing E.G7-OVA tumor and extended mice survival. All the results show that immunization with PDs/OVA nanoparticles elicited more effective OVA-specific cellular immune responses. PDs could serve as promising vaccine delivery systems for cancer immunotherapy.